2023
DOI: 10.1152/japplphysiol.00670.2022
|View full text |Cite
|
Sign up to set email alerts
|

Venous capacity and compliance in hypertensive adults: influence of hypoxia and hyperoxia

Abstract: In hypertension, the cardiorespiratory responses to peripheral chemoreflex activation (hypoxia) and inactivation (hyperoxia) are reportedly augmented, but the impact on peripheral venous function is unknown. We tested the hypothesis that in hypertensives, both hypoxia and hyperoxia evoke more pronounced changes in lower limb venous capacity and compliance, than in age-matched normotensives. In 10 hypertensive [HTN: 7 women; age: 71.7±3.7 yr, mean blood pressure (BP): 101±10 mmHg, mean±SD] and 11 normotensive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…15 A recent study in humans with hypertension reported augmented venomotor responsiveness to hypoxia. 16 A potential causative role of venous neurovascular control is suggested by studies showing that nonselective (ie, arterioles and venules) denervation of the mesenteric 17 and splanchnic 18 vascular beds ameliorated hypertension. However, the specific contribution of venoconstrictor sympathetic drive remains equivocal.…”
mentioning
confidence: 99%
“…15 A recent study in humans with hypertension reported augmented venomotor responsiveness to hypoxia. 16 A potential causative role of venous neurovascular control is suggested by studies showing that nonselective (ie, arterioles and venules) denervation of the mesenteric 17 and splanchnic 18 vascular beds ameliorated hypertension. However, the specific contribution of venoconstrictor sympathetic drive remains equivocal.…”
mentioning
confidence: 99%